Testimonies of Violence during Ethnographic Research: A Look at Vicarious Trauma and Compassion Fatigue - Jousset, Amanda (Swiss Journal of Sociocultural Anthropology, 2025)
This article looks at how anthropologists deal with the effects of witnessing violence. Although anthropologists work in interaction with human beings, they rarely discuss the consequences of these encounters on their mental equilibrium. However, concepts such as vicarious trauma and compassion fatigue, developed in medical and social work literature, do provide some insight into the consequences of exposure to difficult narratives. Based on the author’s research notes on cocoa cultivation in Peru, this article interweaves her experience with that of other researchers. This article proposes to consider these destabilizing effects of empirical research as an integral part of the research process, whatever the topic of the research, and thereby put the well-being of researchers at the heart of the methodology.